REGIONAL DISPARITIES IN SLOVAK AGRICULTURE - Ľubica RUMANOVSKÁ; Zuzana LAZÍKOVÁ; Jarmila LAZÍKOVÁ; Ivan TAKÁČ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Regional disparities can be perceived as a cross-cutting category of many disciplines, but most often they can be perceived as economic differences of regions' level of maturity. Regional disparities in business are addressed mainly by Asian countries. In European countries, research on regional disparities in agriculture is paying less attention. The article focuses its attention on the research of regional disparities in the field of agriculture. The analysis of the series of production and economic indicators showed that, instead of the expected convergence of the development of agriculture in the individual regions of Slovakia, the regions diverged in the monitored period. What is contrary to the European Union's endeavor to ensure convergence of regions under the regional and cohesion policy for 2014-2020.